‘The longest suicide vote in history’: the Labour Party leadership election of 2015 - Dorey, Peter; Denham, Andrew (Palgrave Macmillan, 2016)
The Labour leadership contest of 2015 resulted in the election of the veteran Left-wing backbencher, Jeremy Corbyn, who clearly defeated the early favourite, Andy Burnham. Yet Corbyn enjoyed very little support among Labour MPs, and his victory plunged the PLP into turmoil, particularly as he was widely viewed as incapable of leading the Party to victory in the 2020 general election. Given that, much of the established academic literature on Party leadership contests emphasises the ability to foster unity, and thereby render a party electable, as two of the key criteria for electing a new leader, coupled with overall competence, important questions are raised about how and why the Labour Party chose someone to lead them who clearly does not meet these criteria. We will argue that whilst these are the natural priorities of MPs when electing a new leader, in Corbyn’s case, much of the extra-parliamentary Labour Party was more concerned about ideological conviction and purity of principles, regardless of how far these diverged from public opinion. This was especially true of those who signed-up to the Labour Party following the 2015 general election defeat. Indeed, many of these only did so after Corbyn had become a candidate. This clearly suggests a serious tension between maximising intra-party democracy and ensuring the electability of the parliamentary party itself.